The Influence of Students' Purchase Intention on Modern Retail Products: The Role of Brand Image, Product Variety, and Lifestyle in the Campus Environment - Berliana Mekaratri; Moh. Chairil Asmawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of brand image, product variety, and lifestyle on students' purchase intention toward modern retail products, with a focus on Alfamidi outlets in the vicinity of Muhammadiyah University of Surakarta (UMS). A quantitative approach was employed using an explanatory survey method. The research population was considered unlimited, and the sampling technique used was purposive sampling, resulting in 130 active student respondents. The instrument used was a closed-ended questionnaire, and the data were analyzed using multiple linear regression. The analysis results indicate that brand image (α1 = 0.200; p = 0.018), product variety (α2 = 0.297; p = 0.001), and lifestyle (α3 = 0.302; p = 0.000) each have a significant partial effect on purchase intention. Simultaneously, the three variables have a significant influence on purchase intention, with a coefficient of determination (R2) of 0.657 and a model significance value (Prob. F) of 0.000 (< α 0.01). These findings suggest that students' perceptions of brand, product diversity, and lifestyle play an important role in influencing purchasing decisions in modern retail. The practical implications of this study provide a strategic foundation for retail businesses in designing more adaptive marketing approaches tailored to the characteristics of young consumers in a university setting.